Barriers to engagement: scrutiny gaps in Irish prisons - Valk, Sophie van der (Prison service journal, 2023)
Prisons in Ireland and across the world are subject to a growing range of scrutiny bodies. However, even as such bodies strive to develop best practices there remain inherent challenges related to how best to generate meaningful knowledge about the prison experience. Through analysis of interviews with prisoners in Ireland, this paper explores the barriers to engagement which prisoners face when choosing (or not) to interact with prison oversight mechanisms. These barriers include low expectations of prisons and the ability of prisons to change, low awareness and trust in oversight bodies and their role in protecting prisoners’ rights, as well as concerns about the consequences of speaking up and what is worth speaking up about. This final barrier termed wasted agency, can place a limit on when and what prisoners are willing to speak to bodies about and what is considered worth taking a risk for. Recognizing the role these barriers play in who and what is referred to prison oversight bodies can shine a light on scrutiny gaps which may arise and differences in communication between oversight bodies and those they are intended to protect.